Mapping geographical inequalities in access to drinking water and sanitation facilities in low-income and middle-income countries, 2000–17 - Local Burden of Disease WaSH Collaborators (The Lancet, 2022)
This article was published in The Lancet Global Health by Elsevier [© 2020 The Author(s). Published by Elsevier Ltd. This is an Open Access article under the CC BY 4.0 license] and the definite version is available at: https://doi.org/10.1016/S2214-109X(20)30278-3 The Journal's website is at: https://www.sciencedirect.com/science/article/pii/S2214109X20302783?via%3Dihub